(untitled) (Journal of Pharmaceutical Negative Results, 2022)
Objective: This study's objective was to identify Pseudomonas aeruginosa, which was isolated from clinical samples (burn and wound) at Al Muthanna hospitals in Iraq by sequencing the 16S rRNA gene and studying its resistance to some antibioticsMethods: Fifty-five bacterial isolates were obtained from clinical samples (burns and wounds) from Al Muthanna hospitals in Iraq, identified as P. aeruginosa using enrichment selectivemedia and biochemical tests. For identification of P. aeruginosa at the DNA level, DNA was extracted from P. aeruginosa using the genomic DNA extraction kit. The conventional PCR technique is carried out based on a specific primer for 16S rRNA. The amplified PCR products were sequenced by Macrogen Inc. in Seoul, South Korea. The susceptibility of P. aeruginosa isolates to 20 different antibiotics was investigated according to the (CLSI).Results: 55 P. aeruginosa isolates produces various colours on enrichment selective media, including blue, green, and yellow-green. Sequence analysis by BLASTn displayed 10 local isolates had 96 % similarity to the detected P. aeruginosa strain recoded earlier in the GenBank the rest of the local analysis samples were also recognised as P. aeruginosa with homology ranging from (90-95.77%) when compared to already registered and listed in the GenBank bacterial strains. Most isolates showed high resistance degrees to ampicillin, ampicillin/sulbactam, clindamycin, tetracycline, and rifampin, nalidixic acid, streptomycin, ceftriaxone, gentamycin, cefotaxime, ceftazidime, pipercilin, tobramycin, and ciprofloxacin. It was moderately resistant to norfloxacin, meropenem, imipenem, pipracilin, and tazobactam.